Analisis Kemampuan Literasi Numerasi Siswa dalam Menyelesaikan Soal AKM Ditinjau dari Gaya Belajar dan Self Esteem - Mardhiyana, Dewi; Najibufahmi, Muhamad (SJME (Supremum Journal of Mathematics Education), 2025)
This study aims to analyze students' numeracy literacy skills in solving AKM questions in terms of learning style and self-esteem. Apart from that, to find out the factors that cause students' difficulties in solving numeracy literacy skills questions when viewed from varying learning styles and self-esteem. This research is qualitative research with a descriptive approach. Data collection methods were carried out using tests, questionnaires and interviews. The test is used to measure students' numeracy literacy skills which consists of 4 domains and each domain consists of 3 questions, so there are 12 questions. The questionnaire is used to determine students' learning styles according to David Kolb and students' self-esteem categories. Interviews is used to determine factors causing students' difficulties in solving numeracy literacy skills questions. The data analysis technique uses concepts according to Miles and Huberman, namely data reduction, data display, and conclusion drawing/verification. The research results showed that students' numeracy literacy skills in solving AKM questions are in the quite good category. The factors that cause students' difficulties in solving numeracy literacy skills questions are that students are not careful enough, don't want to try, don't understand the questions, can't find a way to solve them, can't solve problems, and make mistakes when doing calculations.